Pursuing a Career in Translation for Indonesian Speakers - Pesurnay, Michael Alfredo; Lestari, Sisilia Endah; Reno, Wasisti Argo Tyas; Bram, Barli (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2016)
Since becoming a translator needs certain skills and qualifications, this article providesdetailed information on the process from starting and developing a career in translation.Based on accessible references and a limited interview with a professional translator, somerecommendations are in place. A perspective translator has to go through the followingprocedures; (1) acquisition and development of language competence, (2) translationcompetence development, (3) translation market, and (4) career development. Being asuccessful translator, one should have known how to start, including how to tell people theirexistence and knowing their skills and abilities in translation; how they manage their personaland financial management, how they deal with customers, and what to do if things go wrong. Keywords: translation career, Indonesian speaker, translation management